AT&T : practical steps for aligning information technology with business strategies : how to achieve a competitive advantage - Boar, Bernard H. (John Wiley New YorkUS, 1994)
Focuses on 2 themes viz. the nature of strategic alignment; and secondly, the actions that need to be taken to achieve business+information technology (IT) alignment. Provides techniques for overcoming architecture problems, including a diagramming technique for drawing clear blue prints. Emphasises the importance of proper design of the business economy in which the IT function operates; and suggests specific actions for ensuring timely and high-quality delivery of applications.